The Relation of Students’ Choice of Private Higher Education and Marketing Strategies in Bosnia and Herzegovina - Ozbal Okai (Evropejskij Issledovatelʹ, 2015)
Severe market conditions and advancing technology demand a well-planned and a strategic marketing approach in all sectors as well as in education sector. This study examined the relationship between the students’ choice and the marketing strategies of private higher education (HE) in Bosnia and Herzegovina (BIH). To perceive this relation, we chose one of the private universities in Sarajevo. The study is based on a student survey which employed a questionnaire of 55 questions under 4 sub-groups and was done by 146 students. The first step of the questionnaire was determining the motives of the students to attend a private HE institution. The next part was to investigate the information sources of the students. These two steps followed the understanding of the evaluation criteria and the decision process of the students. Finally, the survey was concluded with the post enrollment observations of the students. The data obtained analyzed by SPSS software. The results revealed a strong consistency. The students were willing to have quality education and improve themselves via HE. They were using internet as a prior information source but would not make a final decision without parents’ confirmation. The overall satisfaction of the students showed that our subject university communicates with the target groups efficiently and enjoys the benefits of positive ‘word of mouth’ marketing. Finally, we addressed the marketing strategies that we reaped throughout the study to suggest a course of action to private HEIs in the conclusion part.